2018
DOI: 10.1242/dmm.032060
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal pericytes promote subretinal fibrosis after experimental photocoagulation

Abstract: Subretinal fibrosis results in local destruction of retinal structures and permanent vision loss, representing the end stage of neovascular age-related macular degeneration (AMD). Histological examination of fibrotic specimens from AMD patients has uncovered a wide range of cellular and acellular components. However, their origins and roles in fibrosis remain largely unexplored. Using a laser-induced photocoagulation model with collagen 1α1-GFP reporter mice, we demonstrate, by cell-lineage tracing, that peric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…Macrophages may also give rise to myofibroblasts via macrophage-myofibroblast transition (MMT) in subretinal fibrosis secondary to nAMD [202]. Choroidal pericytes may represent another potential source of myofibroblast precursors where they have been found to infiltrate CNV and transdifferentiate into collagen I-expressing cells in a photocoagulation CNV mouse model [203].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Macrophages may also give rise to myofibroblasts via macrophage-myofibroblast transition (MMT) in subretinal fibrosis secondary to nAMD [202]. Choroidal pericytes may represent another potential source of myofibroblast precursors where they have been found to infiltrate CNV and transdifferentiate into collagen I-expressing cells in a photocoagulation CNV mouse model [203].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Various choroidal stromal cells have been detected in the experimental model CNV and fibrosis [28]. A recent study in a mouse model of CNV/fibrosis has shown that choroidal pericytes can infiltrate the CNV and differentiate into collagen 1-expressing cells [46]. The choroidal stromal cells may be a potential source of myofibroblast precursors.…”
Section: Molecular Mechanism Of Macular Fibrosis In Namdmentioning
confidence: 99%
“…The specimens were mounted in mounting medium, including DAPI (1:500, Vector Laboratories, Burlingame, CA, USA), and examined under a fluorescence microscope (BIOREVO, Keyence, Tokyo, Japan). The number of nucleus surrounded by NG-2 positive signals, corresponding to pericytes, are counted unbiasedly in five consecutive tissue sections, as previously described [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since PDGFR-β signaling is involved in pericyte activation, proliferation, and migration, blockade of pericyte activation with PDGFR inhibitor attenuated interstitial kidney fibrosis in mice [ 14 ]. Additionally, it has been reported that pericytes expressing PDGFR-β infiltrate into the subretinal space after CNV induction and subsequently contribute to subretinal fibrosis formation in mice [ 18 ]. Interestingly, levels of PDGFs were reported to positively correlate with fibrosis in patients with proliferative diabetic retinopathy (PDR) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%